Efficacy of Balloon Tamponade in Postpartum Hemorrhage - Sara Yousaf, Noreen Nasim, Safia Yasmin, Hafiz Naveed Anjum (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: An estimated loss of more than 500 mL of blood after vaginal delivery and more than 1000 mL of blood following caesarean delivery from the birth canal within 24 hours is considered primary postpartum haemorrhage (PPH). Rightfully termed the "obstetrician’s nightmare," primary postpartum haemorrhage remains a major contributor to maternal mortality and morbidity in underdeveloped countries like Pakistan, where it accounts for 21-31% of maternal deaths. As a result, investigating PPH management strategies is vital. Objectives: To determine the efficacy of intrauterine balloon tamponade in the management of post-partum hemorrhage Study Design: Descriptive study Study Setting: Department of Obstetrics and Gynecology, Sheikh Zayed Medical from 21st May 2021 till 20th November 2021. Methods: Total 126 women aged 18-35 years, parity 1-6 and 31-41 weeks of gestation, who develop atonic post-partum hemorrhage not responding to uterotonics following normal vaginal delivery or caesarean section were enrolled using non-probability consecutive sampling technique. Women having postpartum hemorrhage were treated with balloon tamponade to stop bleeding. Efficacy was noted after 06 hours of procedure. Data was entered and analyzed using SPSS 25. Results: In this study total 126 patients were enrolled with mean age of 25.6±5.3 years. Mean gestational age was 38.2±3.2 weeks. Mean blood loss was 1032.1±379.6 ml. Mean parity was4.1±1.3. Most of patients had middle education i.e. 33.3%. Majority of patients belonged to middle socioeconomic status i.e. 47.6%. There were 41.3% patients who were booked and 2 had regular antenatal visits. Vaginal delivery was done in 55.6% patients. Balloon tamponade was effective in 81% patients. Practical Implication: Since balloon tamponade is a relatively new procedure, there is little information about its efficacy compared to the more traditional method of uterovaginal packing in Pakistan. Conclusion: Balloon tamponade is effective in stopping postpartum hemorrhage. The success rate (81%) of balloon tamponade in preventing PPH is high. It’s convenient for use in situations with a higher risk of PPH. Keywords: Postpartum Hemorrhage, Balloon Tamponade, Delivery, Efficacy, Blood Loss, Management